ANALYSIS THE ROLE OF WORK-LIFE BALANCE TOWARDS EMPLOYEE ENGAGEMENT IN PT. TIRTA INVESTAMA AIRMADIDI - Runtukahu, Gloria Maya; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: In the global era of competition, the potential employee holds the important role in achieving the company’s goals. Therefore, companies need to build employee engagement, it will drive employee to high performance and work optimally for the company and it will often waste their social and family time. In this case, work-life balance strategies are needed to be implemented. PT. Tirta Investama Airmadidi is one of advanced company that has many employees. This research is aimed to analyze the work-life balance condition of employees and how its role towards employee engagement in PT. Tirta Investama Airmadidi. This research is a qualitative research using case study analysis method that gathering primary data from in-depth interview of 15 informants. The results of this research show that PT. Tirta Investama Airmadidi has employees who have been engaged themselves to the company. The engagement that built of employees have a high level in strength, dedication and absorption aspects due to time balance, involvement balance and satisfaction balance that makes their work life and personal life balance. The researcher recommend that the company build more employee who can engaged themselves with the company by paying attention to employees’ work-life balance. Keywords: work-life balance, employee engagement